Answer:
y > 2x - 2 and x + 4y > -12
Step-by-step explanation:
Given
Let the first line be A. So, the coordinates are:
(-4,-2) and (0,-3)
Let the second line be B. So the coordinates are:.
(0,-2) and (2,2)
Required
Complete the inequality
[First, we need to determine the slope (m) of A]
m = (y2 - y1)/(x2 - x1)
[Where]
(x1,y1) = (-4,-2) and (x2,y2) = (0,-3)
[The equation becomes]
m = (-3 -(-2))/(0 - (-4))
m = (-3 + 2)/(0 + 4)
m = (-1)/4)
m = -¼
[Next, we calculate the equation of A using]
y - y1 > m(x - x1)
[We used > because from the question, we understand that everything above the line is shaded.]
So, the inequality becomes.
y - (-3) > -¼(x - 0)
y + 3 > -¼(x)
y + 3 > -¼x
[Multiply through by 4]
4y + 12 > -x
[Add x to both sides]
x + 4y + 12 > x - x
x + 4y + 12 > 0
[Subtract 12 from both sides.]
x + 4y + 12 -12 >0 -12
x + 4y > -12
[We do the same operations for line B]
First, we need to determine the slope (m)
m = (y2 - y1)/(x2 - x1)
Where
(x1,y1) = (0,-2) and (x2,y2) = (2,2)
[The equation becomes]
m = (2 -(-2))/(2 - 0)
m = (2 + 2)/(2-0)
m = 4/2
m = 2
[Next, we calculate the equation of B using]
y - y1 > m(x - x1)
[We used > for the same reason as line A]
So, the inequality becomes.
y - (-2) > 2(x - 0)
y + 2 > 2(x)
y + 2 > 2x
[Subtract 2 from both sides]
y > 2x - 2
[Hence, the complete linear inequalities are:]
y > 2x - 2 and x + 4y > -12